Singular Integral Equations of Convolution Type with Cosecant Kernels and Periodic Coefficients. (9th October 2017) - Li, Pingrun
Abstract : We study singular integral equations of convolution type with cosecant kernels and periodic coefficients in classL 2 [ - π, π ] . Such equations are transformed into a discrete jump problem or a discrete system of linear algebraic equations by using discrete Fourier transform. The conditions of Noethericity and the explicit solutions are obtained by means of the theory of classical boundary value problem and of the Fourier analysis theory. This paper will be of great significance for the study of improving and developing complex analysis, integral equations, and boundary value problems.